THE EFFECTS OF APPLYING RECIPROCAL TEACHING METHOD TO THE STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION - Ambar Wulan Sari (English Teaching and Linguistics Journal (ETLiJ), 2021)
The objective of the research was to find out the effects of applying reciprocal teaching method to the students’ achievement in reading comprehension. The study applied the experimental research method. The population was the 2019-2020 Semester II English Department FKIP UMSU which consist of 64 students. All of the population was taken as the total sample. The students were divided into two groups which each group consist of 32 students, namely experimental and control group. The experimental group was taught by applying reciprocal teaching method while the control was taught by using conventional method. The instrument used in this study was the test with multiple choice questions. The multiple choice test consisted of 20  items, each correct answer was scored 5 so the highest score was 100, while incorrect answer was given 0 score. The data was analyzed by using t-test formula. The findings show that the value of tobserve = 3.50. the value ttable = 2.00 in α = 5% = 0.05. It shows that tobserve  > ttable (3.50 > 2.00). It means that students who were taught by applying reciprocal teaching method was better than those who were taught by using conventional method. Based on the findings above, it can be said that alternative hypothesis (Ha) was accepted.